The Impact of Bullying Behaviour on the Mental Health of Santri: A Case Study at Pondok Pesantren Islahuddin Kediri - Oktaviani, Ranis; Febria Syifa’unnufus (Tinta Emas Institute, 2023)
The aims of this study were (1) to describe the forms of bullying behavior on the mental health of students at the Islahuddin Islamic Boarding School, Kediri. (2) Describe the impact of bullying behavior on the mental health of students at the Islamic boarding school Islahuddin Kediri. (3) Describe the efforts of Islamic boarding schools in reducing bullying behavior in Islamic boarding schools Islahuddin Kediri. The research method used in this research is a qualitative approach with the type of case study research. To find data, researchers used interview, observation and documentation techniques. The results of the study found that (1) forms of verbal bullying behavior that occurred at the Islahuddin Islamic Boarding School Kediri were slandering the victim and the victim's parents, mocking, threatening, and saying dirty words. While the forms of physical bullying that occur are hitting, taking things, and pinching; (2) the impact of bullying on mental health, namely the victim of bullying becomes quiet, weak, afraid when meeting the perpetrator, tired of the perpetrator's treatment of him, becomes very gloomy, and also not enthusiastic about learning; (3) the cottage's efforts in reducing bullying behavior are advising, admonishing, providing early religious education to students, providing strong character education through learning activities, filling spare time with something useful, such as extracurricular scouts, hadroh, and tahfidz Al-Qur' an.